2015
DOI: 10.1039/c5cp00027k
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of gas phase oxalic acid with ammonia and its atmospheric implications

Abstract: Oxalic acid is believed to play an important role in the formation and growth of atmospheric organic aerosols. However, as a common organic acid, the understanding of the larger clusters formed by gas phase oxalic acid with multiple ammonia molecules is incomplete. In this work, the structural characteristics and thermodynamics of oxalic acid clusters with up to six ammonia molecules have been investigated at the PW91PW91/6-311++G(3df,3pd) level of theory. We found that oxalic acid forms relatively stable clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 90 publications
2
49
0
Order By: Relevance
“…58 [68][69][70][71] The BH method includes two steps. Therefore, searching large clusters by chemical intuition is very difficult.…”
Section: Methodsmentioning
confidence: 99%
“…58 [68][69][70][71] The BH method includes two steps. Therefore, searching large clusters by chemical intuition is very difficult.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from NH 3 , amines are among the few basic compounds present in the actual atmosphere, and as such can be expected to bind strongly to H 2 SO 4 or other nucleation precursors. All the eld, laboratory, and modelling studies have suggested that the amines might play a signicant role in the formation and subsequent growth of aerosol particles; 10,27,28 some amines may even be more effective than NH 3 at enhancing the particle formation. In the recent quantum chemical study involving several amines possibly existing in the atmosphere, it was pointed out that they could form more strongly bound structures with H 2 SO 4 than NH 3 .…”
Section: 10-13mentioning
confidence: 99%
“…Gibbs free energy changes are effective for evaluating the strength of the intermolecular interaction and the spontaneity of the process of the cluster formation, 28 and are therefore used to understand the interaction of methanesulfonate with NH 3 or amine and their hydration. The relative single-point energies, DE (0 K), of the (MSA À )(NH 3 )(H 2 O) n (n ¼ 0-3) clusters are calculated using the following eqn (2) and (3).…”
Section: Thermodynamics Of the Cluster Formationmentioning
confidence: 99%
“…1993), is the water-soluble organic acid, so it has high concentration in aerosols (Kawamura et al, 2013;van Pinxteren et al, 2014;Deshmukh et al, 2016;Wang et al, 2016). In addition to accumulating in aerosols, oxalic acid, as an organic acid in the gas phase, has been found to enhance the new particle formation (NPF) (Xu et al, 2010;Weber et al, 2012;Xu and Zhang, 2012;Weber et al, 2014;Peng et al, 2015;Miao et al, 2015;Zhao et al, 2016;Chen et al, 2017;Xu et al, 2017;Arquero et al, 2017;Zhang, 2010). Theoretical studies about the effect of oxalic acid on atmospheric particle nucleation and growth have 5…”
Section: Introductionmentioning
confidence: 99%
“…shown that it can form stable complexes with water (Weber et al, 2012), sulfuric acid (Xu et al, 2010;Xu and Zhang, 2012;Miao et al, 2015;Zhao et al, 2016), ammonia (Weber et al, 2014;Peng et al, 2015) and amines (Chen et al, 2017;Xu et al, 2017;Arquero et al, 2017) via intermolecular hydrogen bond. The potential of oxalic acid for contributing to the NPF is mainly attributed to its capability of forming hydrogen bond with hydroxyl and/or carbonyl-type functional group.…”
Section: Introductionmentioning
confidence: 99%